Proprotein-processing endoproteases PC6 and furin both activate hemagglutinin of virulent avian influenza viruses. - Horimoto, T (1994)
Among the proprotein-processing subtilisin-related endoproteases, furin has been a leading candidate for the enzyme that activates the hemagglutinin (HA) of virulent avian influenza viruses. In the present study, we examined the cleavage activity of two other recently isolated ubiquitous subtilisin-related proteases, PACE4 and PC6, using wild-type HA of A/turkey/Ireland/1378/83 (H5N8) and a series of its mutant HAs. Vaccinia virus-expressed wild-type HA was not cleaved in human colon adenocarcinoma LoVo cells, which lack active furin. This processing defect was corrected by the expression of furin and PC6 but not of PACE4 and a control wild-type vaccinia virus. PC6 showed a sequence specificity similar to that with the endogenous proteases in cultured cells. When LoVo cells were infected with a virulent avian virus, A/turkey/Ontario/7732/66 (H5N9), only noninfectious virions were produced because of the lack of HA cleavage. However, when the cells were coinfected with vaccinia virus that expressed either furin or PC6, the avian virus underwent multiple cycles of replication, indicating that both furin and PC6 specifically cleave the virulent virus HA at the authentic site. These data suggest that PC6, as well as furin, can activate virulent avian influenza viruses in vivo, implying the presence of multiple HA cleavage enzymes in animals.